2021
DOI: 10.2319/060820-527.1
|View full text |Cite
|
Sign up to set email alerts
|

Orthopedic outcomes of hybrid and conventional Hyrax expanders:

Abstract: Objectives To compare the effects of a hybrid miniscrew-supported expander versus a conventional Hyrax (CH) expander in growing patients. Materials and Methods Forty patients were randomized into two groups: a hybrid Hyrax (HH) expander group using a Hyrax expander with two miniscrews and a CH expander group. The final sample had 18 subjects (8 female, 10 male; initial age of 10.8 years) in the HH group and 14 subjects (6 fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
0
9
0
7
Order By: Relevance
“…Garib et al found similar dental effects for hybrid expanders incorporating premolar extensions and TB expanders in growing patients. 12 Gunyuz Toklu et al compared a four-band Hyrax with a hybrid appliance and noted a decrease in buccal cortical bone thickness at the premolars only in the Hyrax group, when the appliance was anchored to those teeth. 11 Pangrazio-Kulbersh et al assessed bonded and two-banded Hyrax appliances and observed a reduction of >0.5 mm in the BABT at the first premolars and first molars in both appliance groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Garib et al found similar dental effects for hybrid expanders incorporating premolar extensions and TB expanders in growing patients. 12 Gunyuz Toklu et al compared a four-band Hyrax with a hybrid appliance and noted a decrease in buccal cortical bone thickness at the premolars only in the Hyrax group, when the appliance was anchored to those teeth. 11 Pangrazio-Kulbersh et al assessed bonded and two-banded Hyrax appliances and observed a reduction of >0.5 mm in the BABT at the first premolars and first molars in both appliance groups.…”
Section: Discussionmentioning
confidence: 99%
“…6 A recent systematic review showed that there are few studies which reported the effects of different types of expanders and skeletal age. 10 Although several studies describing the effects of hybrid expanders on RME and SARME have been published, 5,[11][12][13][14] studies based on the skeletal growth stage are warranted in order to justify the common use of tooth-bone-borne (hybrid) maxillary expansion during different growth periods. The aim of this clinical, two-centre, cone beam computed tomography (CBCT) study was to investigate the differences between conventional tooth-borne (TB) and tooth-bone-borne (hybrid) RME in the pubertal and postpubertal stages, and also in surgically-assisted RME (SARME) in young adults in regard to dentoskeletal effects and buccal alveolar bone levels.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Previous studies have demonstrated that dental measurements produced from 3D digital models are equivalent to those obtained from conventional models in the three planes of space, require less time, and are one-to-one measurements. [16][17][18][19][20] There are still certain restrictions on the capacity to detect and demonstrate adequate precision when accumulating contact intensities in bite registrations, even if the new intraoral scanning approach has the potential to do away with the requirement for impressions and the time necessary to generate models. 21,22 Because there is no evidence concerning the differences between a hybrid hyrax (HH) and tooth borne expander [23][24][25] , As a result, the goal of this study was to assess changes in digital study casts between two types of RME, tooth borne versus hybrid expander, using 3D virtual models scanned using a 3Shape laser scanner.…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, a utilização da TCFC com voxel de 0.2 mm foi essencial para avaliar os efeitos dentais e esqueléticos após a ERM. Dessa maneira, a TCFC foi uma ferramenta essencial para avaliar os efeitos pós ERM, assim como foi realizado anterioremente (Garib et al, 2005;Garib et al, 2006;Rungcharassaeng et al, 2007;Garret et al, 2008;Baratieri et al, 2010;Christie et al, 2010;Weissheimer et al, 2011;Pangrazio et al, 2012;Brunetto et al, 2013;Sygouros et al, 2014;Gunyuz et al, 2015;La blonde et al, 2017;Garib et al, 2021).…”
Section: Discussionunclassified
“…Cheung et al (2020), encontraram um maior aumento do volume aéreo em pacientes tratados com o Hyrax híbrido, quando comparados com pacientes tratados com dispositivos dentossuportados. Garib et al (2021), observaram maiores efeitos esqueléticos na cavidade nasal e nas dimensões da maxila, em pacientes tratados com o Hyrax híbrido.…”
Section: Lista De Figurasunclassified